Backward transfer in second language learning/teaching – the research status of the phenomenon in the context of Polish and foreign research - Dyderska, Aleksandra (Papers in Linguistics, 2025)
This article is a overview and theoretical study focusing on backward transfer (BT), defined as the influence of a foreign language on the first language (L2–L1) during foreign language learning. The aim of the article is to review and systematize terminological findings on BT, to present research tools used in studies of this phenomenon, and to analyze their potential implementation in Poland. The topic is addressed due to the novelty of BT in contact linguistics, particularly in Poland, where systematic research is limited due to methodological challenges. The article reviews the current state of BT research and assesses the effectiveness of existing methods. Comparative analysis of domestic and international research highlights reasons behind implementing different approaches. The findings lead to two main conclusions. First, differences in research techniques arise from factors such as types of multilingualism in a given region, the level of immersion in the foreign language and culture, L1–L2 similarity, and access to appropriate research groups. Second, major current challenges include developing methodologies to detect and characterize BT, identifying factors affecting its presence, and evaluating its consequences.